C1q Regulates Horizontal Cell Neurite Confinement in the Outer Retina - Burger, Courtney A.; Jiang, Danye; Li, Fenge; Samuel, Melanie A. (Frontiers in Neural Circuits, 2020)
During development, neurons generate excess processes which are then eliminated in concert with circuit maturation. C1q is the initiating protein in the complement cascade and has been implicated in this process, but whether C1q-mediated elimination is targeted to particular neural compartments is unclear. Using the murine retina, we identify C1q as a specific regulator of horizontal cell neurite confinement. Subsets of horizontal cell dendritic and axonal neurites extend far into the outer retina suggesting that complement achieves both cellular and subcellular selectivity. These alterations emerge as outer retina synapses become mature and are accompanied by a reduction in adult visual function. C1q expression is restricted to retina microglia, and the loss of C1q results in decreased microglia activation. This pathway appears independent of the C3a receptor (C3aR) and complement receptor 3 (CR3), as horizontal cells are normal when either protein is absent. Together, these data identify a new role for C1q in cell and neurite-specific confinement and implicate microglia-mediated phagocytosis in this process.